Marma: A New Musical Experimental | Marma: Sebuah Karya Baru Musik Eksperimental - I Dewa Gede Bayu Agastya; I Ketut Sudhana (Pusat Penerbitan LPPMPP ISI Denpasar, 2022)
The sensitivity of each human being in capturing cosmic vibrations through the subconscious mind of each is different. Some catch it with full awareness and some with half awareness. The combination of the two is what in Balinese is called